Кризата на общността - Вичева, Виолета (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2021)
The concept of community is considered in a sociological, philosophical and cultural context, tracing the transformation that the idea of community undergoes in the development from traditional to post-traditional society. On this theoretical foundation is based the analysis of seven works from the latest German-language fiction, which examines the literature representation of the community. Its conclusions are again correlated to the theory in order to contribute to the knowledge of the community.